Diskriminasi Tokoh Perempuan dalam Novel Silariang Karya Oka Aurora - Harlina Harlina; Sitti Aida Azis; Amal Akbar (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study aims to describe the forms of discrimination experienced by female characters based on Marginalization, Stereotypes, Subordination, Violence, and Overload. This research discusses in more detail the prohibition of discriminating against women in any form. The data in this study are in the form of sentences and words which are included in the form of discrimination against women. The source of the data in this study is the reading of the novel Silariang by Oka Aurora. The data in the study were collected using reading techniques, listening techniques, and note-taking techniques. The results of this study indicate that there is an act of discrimination against female characters in the silariang novel by Oka Aurora which is studied based on the theory of Apriandra, Sarah and Krisnan Hetti 2021 and then there are elements of acts of discrimination, namely: Marginalization does not give the right to express opinions and does not have the right to vote life partner, stereotypes, subordination, violence such as sexual violence due to arranged marriages and excessive burdens. The results of this study can be concluded that it is not only social status that causes discrimination but with the existence of culture and customs that must be inherited, guarded and firmly held by the parents of female figures, discrimination occurs so that actions against adat with silariang become the only way to break through solid walls of nobility, but in the end the blue blood becomes red blood too.